A Comparison of Classical and H-Type Bovine Spongiform Encephalopathy Associated with E211K Prion Protein Polymorphism in Wild-Type and EK211 Cattle Following Intracranial Inoculation - Moore, S. Jo; West Greenlee, M. Heather; Smith, Jodi D.; Vrentas, Catherine E.; Nicholson, Eric M.; Greenlee, Justin J. (Frontiers in Veterinary Science, 2016)
In 2006, a case of H-type bovine spongiform encephalopathy (BSE-H) was diagnosed in a cow that was associated with a heritable polymorphism in the bovine prion protein gene (PRNP) resulting in a lysine for glutamine amino acid substitution at codon 211 (called E211K) of the prion protein. Although the prevalence of this polymorphism is low, cattle carrying the K211 allele may be predisposed to rapid onset of BSE-H when exposed or to the potential development of a genetic BSE. This study was conducted to better understand the relationship between the K211 polymorphism and its effect on BSE phenotype. BSE-H from the US 2006 case was inoculated intracranially (IC) in one PRNP wild type (EE211) calf and one EK211 calf. In addition, one wild type calf and one EK211 calf were inoculated IC with brain homogenate from a US 2003 classical BSE case. All cattle developed clinical disease. The survival times of the E211K BSE-H inoculated EK211 calf (10 months) was shorter than the wild type calf (18 months). This genotype effect was not observed in classical BSE inoculated cattle (both 26 months). Significant changes in retinal function were observed in H-type BSE challenged cattle only. Cattle challenged with the same inoculum showed similar severity and neuroanatomical distribution of vacuolation and disease-associated prion protein deposition in the brain, though differences in neuropathology were observed between E211K BSE-H and classical BSE inoculated animals. Western blot results for brain tissue from challenged animals were consistent with the inoculum strains. This study demonstrates that the phenotype of E211K BSE-H remains stable when transmitted to cattle without the K211 polymorphism, and exhibits a number of features that differ from classical BSE in both wild type and heterozygous EK211 animals.